Engaging the Local Communities in Developing Cultural Tourism Projects in the Southern Tanzania Tourist Circuit: An Exploratory Study - Emmanuel Samwel Mtani; Yee-Lee Chong; Khor Saw Chin (African Journal of Hospitality, Tourism and Leisure, 2023)
This study intends to explore factors that influence local communities’ participation in cultural tourism activities. Focused ethnographic research based on the Theory of Behaviour Planned (TPB) modeling framework was used to elicit positive and negative belief descriptors that form the basis for local communities’ attitudes, subjective injunctive norms, subjective descriptive norms, and perceived behavioral control. An inductive content analysis was applied to examine the elicited beliefs provided by 30 key informants who were purposely selected among the local community members. The results indicate that nine behavioral beliefs, four normative injunctive beliefs, three normative descriptive beliefs, and ten control beliefs are critical in explaining the formation of local communities’ behaviours in cultural tourism activities in the southern Tanzania tourist circuit. The study adds knowledge and methodological approaches for eliciting belief descriptors with regards to cultural tourism activities among the local communities within the sub-Saharan Africa context. Moreover, it registers evidence-based salient beliefs that form local communities’ attitudes, intentions and behaviours in cultural tourism practices. Tactical measures can then be planned more precisely to intensify the positive belief descriptors and reduce the impact of negative belief descriptors among local communities in developing cultural tourism projects in the southern tourist circuit.